PEMBELAJARAN AL-QUR’AN METODE UMMI: ANALISIS IMPLEMENTASI DAN EFEKTIVITAS MELALUI SYSTEMATIC LITERATURE REVIEW - Al Majid, Faizal; Zain, Afnan (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to systematically analyze the implementation and effectiveness of the Ummi Method in Qur’anic learning across various Islamic educational institutions in Indonesia. The research employed a Systematic Literature Review (SLR) approach by identifying and selecting journal articles published between 2016 and 2025. Based on the predetermined inclusion and exclusion criteria, 15 articles were obtained and analyzed through thematic synthesis. The findings indicate that studies on the Ummi Method are predominantly qualitative in nature, focusing primarily on the implementation process. A consistent pattern of implementation includes teacher certification, the application of the seven structured stages of instruction, and the use of the ten quality assurance pillars as an operational framework. In terms of effectiveness, most studies report improvements in students’ Qur’anic reading skills, particularly in tajwid and reading fluency. However, quantitative findings reveal that the method’s impact is not always statistically significant across all indicators, such as represents a quality-based instructional system whose success is highly dependent on consistent implementation and teacher competence. To strengthen empirical validation of its effectiveness, future research should employ quasi-experimental, comparative, and longitudinal design, combining qualitative and quantitative methods to stregthen the findings, along with more standardized evaluation instruments.